The impact of dental care in oral health of children - doi:10.5020/18061230.2011.p10 - Anya Pimentel Gomes Fernandes Vieira; Jamile Pinheiro Karbage (Universidade de Fortaleza, 2012)
Objective: To evaluate the prevalence of dental decay in institutionalized children (shelter) or not (stable family situation), with and without access to dental care, verifying the impact of this in both groups. Methods: The study had 133 participants of both sexes, with the same socioeconomic level and aged 3 to 6 years old, divided into four different groups. Two groups consisted of institutionalized children, one of whom had regular dental treatment and the other not; the other two groups consisted of children from nursery school, one group presenting dental treatment and the other not. Data collection consisted of medical history and clinical examination performed by one researcher properly calibrated. The index of decayed, missing and filled deciduous teeth (dmf-t) was used to determine the prevalence of caries. Results: Data analysis showed statistically significant difference between groups in the dmf-t that, although high for everyone, was significantly lower for those who had dental care (p <0.001). The comparison between shelters and schools also provided statistically different values of dmf-t (p <0.001), as well as the comparison of schools and shelters among themselves (p = 0.012). In addition, we observed that treatment needs in primary dentition were higher than treatment received and, thus, the preventive approach should be highlighted, both in schools and in shelters for the effective reduction of dental caries rates in this population. Conclusion: Institutionalization as factor did not indicate a higher probability of dental decay in children. However, the absence of the dentist turned significantly higher the probability of dental caries' occurrence